Effects of subthalamic nucleus stimulation and levodopa on the autonomic nervous system in Parkinson's disease. Issue 7 (19th March 2007) - Ludwig, Janne; Remien, Piet; Guballa, Christoph; Binder, Andreas; Binder, Sabine; Schattschneider, Jörn; Herzog, Jan; Volkmann, Jens; Deuschl, Günther; Wasner, Gunnar; Baron, Ralf
Abstract : Dysfunctions of the autonomic nervous system (ANS) are common in Parkinson's disease (PD). Regarding motor disability, deep brain stimulation of the subthalamic nucleus (STN) is an effective treatment option in long lasting PD. The aims of this study were to examine whether STN stimulation has an influence on functions of the ANS and to compare these effects to those induced by levodopa. Blood pressure (BP) and heart rate (HR) during rest and orthostatic conditions, HR variability (HRV) and breathing-induced cutaneous sympathetic vasoconstriction (CVC) were tested in 14 PD patients treated with STN stimulation during "ON" and "OFF" condition of the stimulator. The effects of a single dose of levodopa on ANS were tested in 15 PD patients without DBS. STN stimulation had no influence on cardiovascular ANS functions, whereas CVC was significantly increased. In contrast, levodopa significantly lowered BP and HR at rest and enhanced orthostatic hypotension. Further, HRV, skin perfusion and temperature increased after administration of levodopa. Our results suggest that in contrast to levodopa, STN stimulation has only minor effects on autonomic functions. Since less pharmacotherapy is needed after STN stimulation, reduced levodopa intake results in relative improvement of autonomic function in deep brain stimulated PD patients.